2007
DOI: 10.1037/0022-3514.93.4.685
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of daily events and well-being across cultures: When less is more.

Abstract: The authors examined cultural and individual differences in the relation between daily events and daily satisfaction. In a preliminary study, they established cross-cultural equivalence of 50 daily events. In the main study, participants in the United States, Korea, and Japan completed daily surveys on the 50 events and daily satisfaction for 21 days. The multilevel random coefficient model analyses showed that (a) the within-person association between positive events and daily satisfaction was significantly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 95 publications
7
61
1
2
Order By: Relevance
“…Likewise, people who chronically experience many bad events may not be strongly affected by the addition of one more negative life event. Therefore, deviations from a person's typical life events might produce the greatest changes in happiness set points (Headey & Wearing, 1992;Oishi, Diener, Choi, Kim-Prieto, & Choi, 2005). Two important research traditions shed light on when people adapt or do not adapt to negative events.…”
Section: Revision 5: Individual Differences In Adaptationmentioning
confidence: 99%
“…Likewise, people who chronically experience many bad events may not be strongly affected by the addition of one more negative life event. Therefore, deviations from a person's typical life events might produce the greatest changes in happiness set points (Headey & Wearing, 1992;Oishi, Diener, Choi, Kim-Prieto, & Choi, 2005). Two important research traditions shed light on when people adapt or do not adapt to negative events.…”
Section: Revision 5: Individual Differences In Adaptationmentioning
confidence: 99%
“…It also produced in-depth knowledge of the flow experience itself by means of an electronic diary methodology. As in previous studies on positive psychology (Clarke & Haworth, 1994;Oishi, Diener, Choi, Kim-Prieto, & Choi, 2007), we hope that the current study will encourage researchers to use the electronic diary method to investigate the the flow experience, which is fascinating but at the same time tricky to study. Daily Flow Patterns Additional findings concerning the comparison between Models Null, 1 and 2 of enjoyment and also absorption are available on request.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…Averaging across all countries, and in contrast to Suh et al (1996) and Suh et al (1998, Study 1), but consistent with Suh et al (1998, Study 2), they found that positive emotions had nearly twice the influence on life satisfaction as negative emotions. Again, however, and in line with Oishi et al (2007), this overall effect was moderated by culture, such that negative emotions were more important in predicting life satisfaction in individualistic cultures like the US rather than collectivist cultures like China.…”
Section: The Contribution Of Positive and Negative Emotions To Well-bmentioning
confidence: 71%
“…A second study with college students from 40 nations, however, indicated a stronger influence of positive than negative affect on life satisfaction (Suh et al 1998). Oishi et al (2007) extended this work and also examined the relationship between life satisfaction and daily positive and negative events across different cultures. For European Americans each negative event had nearly twice the impact in satisfaction as each positive event, which contrasts with Suh and colleagues' (1996) finding that positive and negative affect had roughly the same impact.…”
Section: The Contribution Of Positive and Negative Emotions To Well-bmentioning
confidence: 96%
See 1 more Smart Citation